2005
DOI: 10.1128/aac.49.7.2693-2700.2005
|View full text |Cite
|
Sign up to set email alerts
|

Population Structure of Enterococcus faecium Causing Bacteremia in a Spanish University Hospital: Setting the Scene for a Future Increase in Vancomycin Resistance?

Abstract: Over an 8-year period (1995 to 2002), 86 Enterococcus faecium blood isolates from 84 patients, of which 54 were ampicillin resistant (AREF) and 32 were ampicillin susceptible (ASEF), were studied in a university hospital (1,200 beds; serving a population of 600,000) in Spain, a country characterized by a near-absence of resistance to vancomycin and very high rates of ampicillin resistance among enterococci. Clonal relatedness by pulsed-field gel electrophoresis (PFGE), antibiotic susceptibility, presence of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
59
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 50 publications
(77 reference statements)
4
59
0
4
Order By: Relevance
“…In our institution, an ampicillin-resistant E. faecium clone (Efm-6, ST18) belonging to HrCC17 and a multiresistant E. faecalis clone (Efc-3, ST17) belonging to HrCC9 were endemic and caused several bacteremic episodes (P. Ruiz-Garbajosa et al, unpublished data). Unlike other clones, they persisted for a long time in certain wards and ICUs in our hospital (7,26). The specific role of the accessory genome involved in clonal persistence is not yet known, but in E. faecalis and E. faecium, hospital-acquired clones have been shown to be enriched in adaptive mechanisms, like the presence of putative virulence genes and novel metabolic pathways (12,13,17,19,27).…”
Section: Discussionmentioning
confidence: 99%
“…In our institution, an ampicillin-resistant E. faecium clone (Efm-6, ST18) belonging to HrCC17 and a multiresistant E. faecalis clone (Efc-3, ST17) belonging to HrCC9 were endemic and caused several bacteremic episodes (P. Ruiz-Garbajosa et al, unpublished data). Unlike other clones, they persisted for a long time in certain wards and ICUs in our hospital (7,26). The specific role of the accessory genome involved in clonal persistence is not yet known, but in E. faecalis and E. faecium, hospital-acquired clones have been shown to be enriched in adaptive mechanisms, like the presence of putative virulence genes and novel metabolic pathways (12,13,17,19,27).…”
Section: Discussionmentioning
confidence: 99%
“…Although E. faecium strains in CC17 are associated with epidemicity in hospitals, there has been a report of a CC17 strain in swine from Portugal (20). Conversely, several studies in Europe have reported finding swine-adapted E. faecium CC5 strains in humans (3,11,12,20,23,30,33).…”
mentioning
confidence: 99%
“…This subpopulation belongs to a distinct genetic lineage labeled clonal complex 17 (CC17) (62) and is associated with the presence of the variant esp gene as part of a pathogenicity island (31) and resistance to ampicillin. Recently, resistance to ciprofloxacin appeared to be associated with ampicillin resistance in genotypically related E. faecium isolates from Norway (25,55,56) and Spain (7).…”
mentioning
confidence: 99%